Practicing Management Information System in Bangladesh - Md. Saiful Bari (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
Management Information Systems is an essential factor in the existing world. The goals of the study to create eagerness for the usage of MIS in every sector in all activities for the betterment of condition. In this paper, we have tried to existing fundamental associated subjects of MIS (that ability literature assessment and it consists of about MIS, Computer software, DBMS, telecommunication and networking), objectives, beneficiary persons, way of finding information, corporation assessment (it consists of historical background, company overview, practices of MIS in this organization), MIS practices and challenges in Bangladesh and ultimately providing likely recommendation.